A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material and preparation method thereof

By developing a multi-system glass fiber reinforced flame retardant low-temperature polyurethane foaming material, combined with the use of specific chemical components and alkali-free continuous glass fiber felt, the problems of existing materials' strength decrease and other performance decreases after the flame retardant performance increase under low temperature conditions are solved, and the comprehensive effect of high strength, low thermal conductivity and excellent flame retardant performance is achieved.

CN117126361BActive Publication Date: 2025-04-25JINAGSU SUNPOWER PIPELINE ENG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311122093.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-04-25
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

The existing foam materials for preparative film tanks show problems of decreased strength and increased thermal conductivity under low temperature conditions. At the same time, other performance indicators will decrease after their flame retardant performance are improved, and the addition of flame retardant increases costs.

Method used

A multi-system glass fiber reinforced flame retardant low-temperature polyurethane foaming material is developed. By combining the use of high-functional isocyanate and diphenylmethane diisocyanate in a specific proportion of reactive flame retardant polyester polyol, reactive flame retardant polyether polyol, high-strength hard foam polyether polyol, high-strength hard foam polyether polyol, surfactant, compound catalyst, flame retardant and multi-system foaming agent, it is combined with the use of high-functional isocyanate and diphenylmethane diisocyanate, and impregnated and foamed with alkali-free glass continuous glass fiber felt.

Benefits of technology

It achieves the maintenance of higher strength and flame retardant performance in low-temperature environments, while reducing the amount of added flame retardant, improving the overall performance indicators of the material, and is suitable for the field of low-temperature insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004426812870000151
    Figure BDA0004426812870000151
  • Figure BDA0004426812870000152
    Figure BDA0004426812870000152
  • Figure BDA0004426812870000161
    Figure BDA0004426812870000161
Patent Text Reader

Abstract

A multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material and preparation method, characterized in that the foam material is composed of reactive flame retardant polyester polyol, reactive flame retardant polyether polyol, high-strength rigid foam polyether polyol, high-toughness rigid foam polyether polyol, high-functionality isocyanate and diphenylmethane diisocyanate, continuous glass fiber felt after surface treatment, multi-system foaming agent, surfactant, composite catalyst, flame retardant. The present invention adopts multi-system foaming agent, reactive flame retardant polyether polyol and polyester polyol, as well as high-strength and high-toughness polyether polyol, and the prepared enhanced cold insulation material can be used in a low-temperature environment, the product density is 60-80kg / m3, the product X and Y direction tensile strength is greater than 1.30MPa, and the product linear expansion coefficient is less than 30x10-6 / K; the product density is 110-150kg / m3, in addition to meeting its national standard, the flame retardant performance reaches the B2 standard specified in GB8624-2012 or above, close to the B1 standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a foaming material, in particular to a low-temperature enhanced polyurethane foaming material, specifically to a multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foaming material and a preparation method and application thereof. Background Art

[0002] Film tanks are used for the storage and transportation of liquefied natural gas. The cold insulation materials used to make film tanks need to maintain their insulation, high compression strength and high stability under low temperature conditions. Conventional cold insulation materials generally have excellent cold insulation properties, but they will shrink and deform at low temperatures, resulting in loss of performance (such as increased thermal conductivity and reduced strength). At the same time, during the construction of film tanks, there are operations with sparks such as welding, which can easily cause safety accidents. Therefore, higher flame retardant performance requirements are required for the materials. By adding flame retardants to improve flame retardancy, other performance indicators of foam materials (such as tensile strength, water absorption, etc.) will decrease a lot; in addition, only increasing the amount of flame retardant polyether polyols and polyester polyols will not only increase the corresponding cost by at least 5 yuan / kg, but also the various performance indicators of the foam materials will be unbalanced.

[0003] At present, there is little research on film tanks, and the research on the hard low-temperature cold-insulating composite materials for preparing film tanks, including the multi-component materials of the reinforcement plates used in film tanks, is only at the preliminary research stage. Summary of the invention

[0004] In view of the contradiction between the comprehensive performance of existing foam materials used in the preparation of film tanks and the inability to meet the requirements of cold preservation and mechanical properties, the present invention invents a multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material, and also provides a corresponding preparation method and application method. The foam material of the present invention has higher strength and better flame retardancy (lower thermal conductivity), longer service life, and is suitable for the insulation field in low temperature environments (-200°C to 0°C).

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A multi-component glass fiber reinforced flame-retardant low-temperature polyurethane foam material, which is firstly made into a foaming material by raw materials including the following parts by weight: 20-50 parts by weight of reactive flame-retardant polyester polyol, 10-30 parts by weight of reactive flame-retardant polyether polyol, 15-30 parts by weight of high-strength rigid foam polyether polyol, 25-35 parts by weight of high-toughness rigid foam polyether polyol, 2-5 parts by weight of surfactant, 1.5-3 parts by weight of composite catalyst, 10-16 parts by weight of flame retardant, 4-15 parts by weight of multi-component foaming agent, and 0.1-1.1 parts by weight of water;

[0007] The foaming material is then mixed with a mixture of high-functionality isocyanate and diphenylmethane diisocyanate (polymeric MDI) in a mass ratio of 1:1.2 to 1:1.5 to obtain a composite material, which is evenly poured on 3 to 10 parts by mass of alkali-free glass continuous fiber felt and completely impregnated with the alkali-free glass continuous fiber felt, and then covered with a film for foaming, demolding, and internal aging to obtain the composite material.

[0008] The product density of enhanced cold insulation material is 60-100kg / m 3 The product density can be adjusted by different ratios between distilled water and foaming agent. The mass ratio of water to foaming agent is (0.9~1.1): (12~15)

[0009] The product density of the enhanced cold insulation material is 110-150kg / m 3 The density of the product is also adjusted by different ratios between distilled water and foaming agent. The mass of water and foaming agent is (0.1~0.3): (4~8)

[0010] The reactive flame-retardant polyester polyol has a hydroxyl value of 150-350 mgKOH / g, a viscosity of 800-16000 mPa·s (25° C.), and a functionality of 2-3.5.

[0011] Specifically, the reactive flame-retardant polyester polyol is one or more of PF-2305A, PF-1605, PF-B23A, PF-2012, PS-2132, PS-2452, and PS-8004A.

[0012] The reactive flame-retardant polyether polyol has a hydroxyl value of 100-400 mgKOH / g, a viscosity of 300-15000 mPa·s (25° C.), and a functionality of 3-5.

[0013] Specifically, the reactive flame retardant polyether polyol is one or more of FR-212, EDS-5083H, EDS-5083L, EDS-5083L-KD, EDS-5083X, and F-7190.

[0014] The high-strength rigid foam polyether polyol has a hydroxyl value of 300-500 mgKOH / g, a viscosity of 300-10000 mPa·s (25° C.), and a functionality of 4.5-8.

[0015] Specifically, the high-strength rigid foam polyether polyol is one or more of H8010, H5820, H8036, NJ-8238, NJ-450L, NJ-6206, and H635SG.

[0016] The high-toughness rigid foam polyol has a hydroxyl value of 100-350 mgKOH / g, a viscosity of 100-500 mPa·s (25° C.), and a functionality of 2-4.

[0017] Specifically, the high-toughness rigid foam polyol is one or more of NJ-210, NJ-310, H310, H210, NJ-3150, and NJ-305.

[0018] The isocyanate (-CNO) content of the high-functionality isocyanate and diphenylmethane diisocyanate mixture is 30-33 wt %, the viscosity is 100-600 mPa·s (25° C.), and the functionality is 2.7-3.5.

[0019] Specifically, the high-functionality isocyanate and diphenylmethane diisocyanate mixture is one or more of PM-200, PM-400, Suprasec 5005, and 44V20L.

[0020] The surfactant is a polyether-polydimethylsiloxane copolymer mixture; preferably one or more of B8443, B8462, B8547, B8490, L-6863, L-6900, AK8860, AK8805, and AK8811.

[0021] The composite catalyst is a combination of at least two of a quaternary ammonium salt catalyst, a trimerization catalyst, a low-odor amine catalyst, and an organic acid salt catalyst;

[0022] Preferably, the composite catalyst is a combination of a quaternary ammonium salt catalyst, a trimerization catalyst, a low-odor amine catalyst and an organic acid salt catalyst in a mass ratio of 1:(0.8-1.8):(0.6-1.2):(3.2-4.6), or a combination of a trimerization catalyst, a low-odor amine catalyst and an organic acid salt catalyst in a mass ratio of (1.5-8):1:(3.5-11), or a combination of a trimerization catalyst and an organic acid salt catalyst in a mass ratio of 1.5:1, or a combination of a quaternary ammonium salt catalyst, a trimerization catalyst or a tertiary amine catalyst in a mass ratio of (0.5-3):1:(1.5-6).

[0023] The quaternary ammonium salt catalyst is selected from at least one of catalysts TMR-2 and TMR-30; the trimerization catalyst is selected from at least one of catalysts K-15 and PC41; the low-odor amine catalyst is selected from at least one of catalysts PC9 and PC5; the organic acid salt catalyst is selected from at least one of catalysts JXP-508 and JXP-509.

[0024] The flame retardant is one or more of triethyl phosphate (flame retardant TEP), tri(2-chloropropyl) phosphate (flame retardant TCPP), tri(2-carboxyethyl) phosphine (flame retardant TCEP), and diethyl ethyl phosphate (flame retardant DMPP), preferably a combination of flame retardant TEP and flame retardant TCPP with a mass ratio of (6-10):(2-6).

[0025] The multi-system foaming agent is one or a mixture of pentafluoropropane, pentafluorobutane, trifluoropropylene, and hexafluorobutene, preferably one or more of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropylene and 1,1,1,4,4,4-hexafluoro-2-butene, more preferably 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropylene and 1,1,1,4,4,4-hexafluoro-2-butene. A mixture of chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene in a mass ratio of (1-6):(2-5):(1-3):(1-2), or a mixture of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene in a mass ratio of (1-3):(1-2):(0-1).

[0026] The alkali-free glass continuous fiber mat is a surface-treated continuous raw fiber mat (made of E glass, with random orientation of continuous filaments, and E glass has high modulus and excellent tensile strength). Each layer of alkali-free glass continuous fiber mat is composed of about 20 layers of slender glass fibers. The apparent density of the alkali-free glass continuous fiber mat is 450-600g / m 2 .

[0027] Preferably, the alkali-free glass continuous fiber mat is one or more of CFM981-450, CFM985-450, CFM985-600, U809-450, and U801-450. The width of CFM981-450, CFM985-450, and CFM985-600 are all 185 cm, the thickness is all 5 mm, and the apparent density is 450 g / m 2 , 450g / m 2 , 600g / m 2 ; U809-450 and U801-450 have a width of 138cm, a thickness of 6mm, and an apparent density of 450g / m 2 , 450g / m 2 .

[0028] Another object of the present invention is to provide a method for preparing the multi-component glass fiber reinforced flame-retardant low-temperature polyurethane foam material, comprising: adding reactive flame-retardant polyester polyol, reactive flame-retardant polyether polyol, high-strength rigid foam polyether polyol, and high-toughness rigid foam polyether polyol into a reactor in the order of low viscosity to high viscosity, adding a surfactant for stirring, and then adding a compound catalyst, a flame retardant, water, and a multi-component foaming agent, stirring to obtain a foam material; pumping the foam material and isocyanate into a high-pressure foaming machine, controlling the temperature of the material to 22±3°C and the pressure to 120±10kPa for high-pressure mixing to obtain a composite material; laying 5 to 8 layers of alkali-free glass continuous fiber felt, evenly pouring the composite material until the alkali-free glass continuous fiber felt is completely impregnated, covering with a film for foaming, demolding, and internal aging to obtain a multi-component glass fiber reinforced flame-retardant low-temperature polyurethane foam material.

[0029] Preferably, after adding the surfactant, pre-stir for 10 to 20 minutes; then add the composite catalyst, flame retardant and water, stir at a speed of 120 r / min for 10 to 25 minutes, and maintain the material temperature at 25°C during the stirring process; then add the multi-system foaming agent, stir at a speed of 80 to 120 r / min for 1 hour to obtain a foamed material.

[0030] The foaming material and isocyanate were mixed evenly and tested. The physical properties of the foaming material (25°C) were met: rising time 50-80s, drawing time 200-400s, non-stick time 600-800s, free foam density 60-130kg / m 3 .

[0031] Preferably, after laying 5 to 8 layers of alkali-free glass continuous fiber mat in the mold, a distribution rod is used to evenly pour the composite material until the alkali-free glass continuous fiber mat is completely impregnated.

[0032] Preferably, the internal ripening temperature is 30±5° C. and the time is 24 hours.

[0033] Another object of the present invention is to provide the use of the multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material in the preparation of film tanks for the storage and transportation of liquefied natural gas.

[0034] The beneficial effects of the present invention are:

[0035] The invention starts from two aspects that affect the low-temperature performance (tensile strength and low-temperature linear expansion coefficient, etc.) of the polyurethane foam material and the flame retardant effect under low chlorine: on the one hand, a high-compression strength rigid foam polyether polyol and a high-tensile strength rigid foam polyol are used to form a polymerization reaction with isocyanate, and the high-compression strength rigid foam polyether polyol contains high-functionality sucrose-type polyol and sorbitol-type polyol, and the high-tensile strength rigid foam polyol contains a more flexible chemical bond (-C=C-), thereby ensuring the mechanical properties of the cold insulation material at low temperatures; on the other hand, reactive polyether polyol and polyester polyol are added, the molecules of which contain nitrogen, phosphorus, and bromine flame retardants, and the modified alkali-free glass continuous fiberglass mat, although the amount of the additive flame retardant is reduced, the effective flame retardant components that react with isocyanate are increased, and the strength and flame retardant grade of the material are improved, thereby ensuring that the cold insulation material has a good flame retardant effect and product stability.

[0036] The polyurethane foam material of the present invention has the characteristics of maintaining higher strength in low temperature environment, more uniform glass fiber felt and high flame retardancy, and is suitable for the field of low temperature insulation. The reinforced cold insulation material prepared by the present invention is used in low temperature environment, and the product density is 60-100kg / m 3 The tensile strength of the product in the X and Y directions is greater than 1.30MPa, and the linear expansion coefficient of the product is less than 30×10 -6 / K; product density is 100-150kg / m 3 In addition to meeting the national standard, the flame retardant performance reaches above the B2 standard specified in GB8624-2012, which is close to the B1 standard. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through specific implementation methods.

[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be fully described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Any technical solutions obtained by equivalent replacement or equivalent transformation should fall within the protection scope of the present invention.

[0039] Example 1.

[0040] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0041] Preparation of foaming material: Take 25kg high-toughness rigid foam polyether polyol H210 (Nanjing Hongbaoli Co., Ltd.), 25kg reactive flame retardant polyether polyol EDS-5083H (Jiangsu Changneng Energy Saving New Material Technology Co., Ltd.), 20kg reactive flame retardant polyester polyol PF-2012 (Qingdao Ruinuo Chemical Co., Ltd.), 30kg high-strength rigid foam polyether polyol NJ-8238 (Jurong Ningwu New Material Co., Ltd.), in order to make the materials fully mixed, add the above ingredients to the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8462 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.5kg catalyst TMR-2, 0.6kg catalyst JXP-508, 0.4kg catalyst K-15, 0.4kg catalyst PC9, 0.1 1.0kg catalyst PC5, 1.0kg catalyst JXP-509 (Air Chemicals, the same below), 8kg flame retardant TEP and 2kg flame retardant TCPP (Yangzhou Chenhua New Materials, the same below), 0.9kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, and the temperature was raised and lowered during the stirring process to ensure that the material temperature was 25°C, and then 12kg mixed foaming agent (1,1,1,3,3-pentafluoropropane (Sinochem Blue Sky Honeywell, the same below), 1,1,1,3,3-pentafluorobutane (Germany Solvay, the same below), 1-chloro-3,3,3-trifluoropropene (Sinochem Blue Sky Honeywell, the same below) and 1,1,1,4,4,4-hexafluoro-2-butene (Chemours Chemical, the same below) were premixed in a mass ratio of 5:4:2:1), the reactor was sealed, and stirred at a speed of 80r / min for 1 hour to obtain a foaming material.

[0042] The material is pumped into a high-pressure foaming machine at a mass ratio of 1:1.2 between the foaming material and PM-400 (a mixture of high-functionality isocyanate and diphenylmethane diisocyanate), and the material temperature is controlled at 22±3°C and the pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0043] The alkali-free glass continuous fiber felt U809-450 was preheated to a temperature of 30±5°C, and 5 layers of alkali-free glass continuous fiber felt (total weight 3.4kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber felt using a distribution rod, and the film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber felt. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 48 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0044] Example 2.

[0045] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0046] Preparation of foaming material: Take 25kg of high-toughness rigid foam polyether polyol NJ-210 (Jurong Ningwu), 20kg of reactive flame-retardant polyether polyol EDS-5083L (Jiangsu Changneng), 25kg of reactive flame-retardant polyester polyol PF-1605 (Qingdao Ruinuo), 30kg of high-strength rigid foam polyether polyol H8036 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg of surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.4kg of catalyst TMR-2, 0.7kg of catalyst JXP-508, 0.45kg of catalyst K-15, 0.35kg of catalyst PC9, 0.1kg catalyst PC5, 1.0kg catalyst JXP-509 (Air Chemicals), 8kg flame retardant TEP and 2kg flame retardant TCPP, 0.9kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, the temperature was raised and lowered during the stirring process to ensure that the material temperature was 25°C, and then 12kg mixed foaming agent (1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene were premixed in a mass ratio of 5:4:2:1) was added, the reactor was sealed, and stirred at a speed of 80r / min for 1 hour to obtain a foamed material.

[0047] The material is pumped into a high-pressure foaming machine at a mass ratio of 1:1.2 between the foaming material and PM-200 (a mixture of high-functionality isocyanate and diphenylmethane diisocyanate), and the material temperature is controlled at 22±3°C and the pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0048] The alkali-free glass continuous fiber felt U809-450 was preheated to a temperature of 30±5°C, and 5 layers of alkali-free glass continuous fiber felt (total weight 3.4kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber felt using a distribution rod, and the film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber felt. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0049] Example 3.

[0050] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0051] Preparation of foaming material: Take 25kg high-toughness rigid foam polyether polyol NJ-310 (Jurong Ningwu New Materials), 15kg reactive flame-retardant polyether polyol EDS-5083X (Jiangsu Changneng Energy Saving), 35kg reactive flame-retardant polyester polyol PS-2132 (Jinling Stepan), 25kg high-strength rigid foam polyether polyol NJ-8238 (Jurong Ningwu New Materials), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8490 (Shanghai Evonik) and 1kg surfactant AK8860 (Nanjing Meisite), pre-stir for 15±5 minutes, then add 0.3kg catalyst PC41, 0.5kg catalyst JXP-508, 0.4kg catalyst K -15, 0.3kg catalyst PC9, 0.1kg catalyst PC5, 0.9kg catalyst JXP-509 (Air Chemicals), 8kg flame retardant TEP and 4kg flame retardant TCPP, 0.95kg distilled water, stirred at a speed of 120r / min for 15±5 minutes, during the stirring process, the temperature was raised and lowered to ensure that the material temperature was at 25°C, and then 13kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 5:5:2:1), the reactor was sealed, stirred at a speed of 80r / min for 1 hour, and a foamed material was obtained.

[0052] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.3 between the foaming material and PM-400, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0053] The alkali-free glass continuous fiber mat CFM985-450 was preheated to a temperature of 30±5°C, and 6 layers of alkali-free glass continuous fiber mat (total weight 4.05kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0054] Example 4.

[0055] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0056] Preparation of foaming material: Take 25kg high-toughness rigid foam polyether polyol H310 (Nanjing Hongbaoli), 20kg reactive flame-retardant polyether polyol EDS-5083H (Jiangsu Changneng), 30kg reactive flame-retardant polyester polyol PS-8004A (Jinling Stepan), 25kg high-strength rigid foam polyether polyol H8036 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8462 (Shanghai Evonik) and 1kg surfactant AK8805 (Nanjing Meisite), pre-stir for 15±5 minutes, then add 0.45kg catalyst PC41, 0.6kg catalyst JXP-508, 0.35kg catalyst K-15, 0. .15kg catalyst PC9, 0.05kg catalyst PC5, 0.9kg catalyst JXP-509 (Air Chemicals), 8kg flame retardant TEP and 4kg flame retardant TCPP, 0.95kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, and the temperature was increased and decreased during the stirring process to ensure that the material temperature was at 25°C, and then 13kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 5:5:2:1), the reactor was sealed, and stirred at a speed of 80r / min for 1 hour to obtain a foamed material.

[0057] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.3 between the foaming material and PM-200, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0058] The alkali-free glass continuous fiber mat CFM985-450 was preheated to a temperature of 30±5°C, and 6 layers of alkali-free glass continuous fiber mat (total weight 4.05kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0059] Example 5.

[0060] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0061] Preparation of foaming material: Take 25kg high-toughness rigid foam polyether polyol NJ-3150 (Jurong Ningwu New Materials), 15kg reactive flame retardant polyether polyol EDS-5083H (Jiangsu Changneng Energy Saving New Materials Technology Co., Ltd.), 40kg reactive flame retardant polyester polyol PF-2305A (Qingdao Ruinuo), 20kg high-strength rigid foam polyether polyol NJ-450L (Jurong Ningwu New Materials), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 3kg surfactant B8457 (Shanghai Evonik) and 1kg surfactant AK8860 (Nanjing Meisite), pre-stir for 15±5 minutes, then add 0.4kg catalyst PC41, 0.4kg catalyst JX P-508, 0.4kg catalyst K-15, 0.1kg catalyst PC9, 0.7kg catalyst JXP-509, 8kg flame retardant TEP and 6kg flame retardant TCPP, 1.0kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, and the temperature was raised and lowered during the stirring process to ensure that the material temperature was 25°C, and then 14kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 5:5:3:1), the reactor was sealed, and stirred at a speed of 80r / min for 1 hour to obtain a foamed material.

[0062] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.4 between the foaming material and PM-400, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0063] The alkali-free glass continuous fiber mat CFM985-450 was preheated to a temperature of 30±5°C, and 7 layers of alkali-free glass continuous fiber mat (total weight 4.73kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0064] Example 6.

[0065] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0066] Preparation of foaming material: Take 25kg high toughness rigid foam polyether polyol NJ-305 (Jurong Ningwu New Materials), 20kg reactive flame retardant polyether polyol F-7190 (Shanghai Xinyue), 35kg reactive flame retardant polyester polyol PF-1605 (Qingdao Ruinuo), 20kg high strength rigid foam polyether polyol H8036 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8462 (Shanghai Evonik) and 1kg surfactant AK8811 (Nanjing Meisite), pre-stir for 15±5 minutes, then add 0.4kg catalyst PC41, 0.4kg catalyst JXP-508, 0.4kg catalyst The mixture was stirred at a speed of 120 r / min for 20±5 minutes, and the temperature was raised and lowered during the stirring process to ensure that the material temperature was at 25°C. Then 14 kg of mixed foaming agent was added (pre-mixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 5:5:3:1), the reactor was sealed, and stirred at a speed of 80 r / min for 1 hour to obtain a foaming material.

[0067] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.4 between the foaming material and PM-200, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0068] The alkali-free glass continuous fiber felt U809-450 was preheated to a temperature of 30±5°C, and 7 layers of alkali-free glass continuous fiber felt (total weight 4.73kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber felt using a distribution rod, and the film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber felt. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0069] Example 7.

[0070] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0071] Preparation of foaming material: Take 25kg high toughness rigid foam polyether polyol NJ-305 (Jurong Ningwu New Materials), 15kg reactive flame retardant polyether polyol EDS-5083L-KD (Jiangsu Changneng), 45kg reactive flame retardant polyester polyol PS-2452 (Jinling Stepan), 15kg high strength rigid foam polyether polyol H8036 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 3kg surfactant B8457 and 2kg surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.4kg catalyst PC41, 0.3kg catalyst JXP-508, 0.3kg catalyst The mixture was stirred at a speed of 120 r / min for 20±5 minutes, and the temperature was raised and lowered during the stirring process to ensure that the material temperature was at 25°C. Then 15 kg of mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 6:4:3:2), the reactor was sealed, and stirred at a speed of 80 r / min for 1 hour to obtain a foamed material.

[0072] The material is pumped into a high-pressure foaming machine at a mass ratio of 1:1.5 between the foaming material and Suprasec5005 (a mixture of high-functionality isocyanate and diphenylmethane diisocyanate), and the material temperature is controlled at 22±3°C and the pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0073] The alkali-free glass continuous fiber mat CFM985-600 was preheated to a temperature of 30±5°C, and 8 layers of alkali-free glass continuous fiber mat (total weight 5.4kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0074] Example 8.

[0075] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0076] Preparation of foaming material: Take 25kg high toughness rigid foam polyether polyol NJ-210 (Jurong Ningwu New Materials), 10kg reactive flame retardant polyether polyol FR-212 (Yantai Wanhua), 50kg reactive flame retardant polyester polyol PF-B23A (Qingdao Ruinuo), 15kg high strength rigid foam polyether polyol H8036 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 3kg surfactant B8462 and 2kg surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.5kg catalyst PC41, 0.2kg catalyst JXP-508, 0.4 kg catalyst K-15, 0.4 kg catalyst JXP-509, 10 kg flame retardant TEP and 6 kg flame retardant TCPP, 1.1 kg distilled water, stirred at a speed of 120 r / min for 20±5 minutes, during the stirring process, the temperature was raised and lowered to ensure that the material temperature was 25°C, and then 15 kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 6:4:3:2), the reactor was sealed, stirred at a speed of 80 r / min for 1 hour, and a foamed material was obtained.

[0077] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.5 between the foaming material and PM-400, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0078] The alkali-free glass continuous fiber mat CFM985-600 was preheated to a temperature of 30±5°C, and 8 layers of alkali-free glass continuous fiber mat (total weight 5.4kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1.

[0079] Example 9.

[0080] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0081] Preparation of foaming material: Take 25kg of high-toughness rigid foam polyether polyol NJ-210 (Jurong Ningwu New Materials) and 75kg of high-strength rigid foam polyether polyol H8036 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 3kg of surfactant B8462 and 2kg of surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.5kg of catalyst PC41, 0.3kg of catalyst JXP-508, 0.5kg of catalyst K-15, 0.6kg of catalyst JXP-509, 15 kg flame retardant TEP and 15kg flame retardant TCPP, 1.3kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, during the stirring process, the temperature was raised and lowered to ensure that the material temperature was 25°C, and then 20kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 7:6:4:3), the reactor was sealed, and stirred at a speed of 80r / min for 1 hour to obtain a foaming material.

[0082] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.5 between the foaming material and PM-400, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0083] The alkali-free glass continuous fiber mat CFM985-600 was preheated to a temperature of 30±5℃, and 7 layers of alkali-free glass continuous fiber mat (total weight 4.73kg) were evenly laid in the mold, and the mold temperature was controlled at 35±5℃; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a cloth rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and placed in a designated insulation warehouse (temperature controlled at 30±5℃) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 1

[0084] Example 10.

[0085] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0086] Preparation of foaming material: Take 25kg of high-toughness rigid foam polyether polyol NJ-210 (Jurong Ningwu New Materials), 25kg of reactive flame-retardant polyether polyol EDS-5083L (Jiangsu Changneng), 25kg of reactive flame-retardant polyester polyol PF-2012 (Qingdao Ruinuo), 25kg of high-strength rigid foam polyether polyol H5820 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg of surfactant B8547 and 1kg of surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.3kg of catalyst TMR-2, 0.3kg of catalyst JXP-508, 0.4kg of catalyst The mixture was stirred at a speed of 120 r / min for 20±5 minutes. During the stirring process, the temperature was raised and lowered to ensure that the material temperature was at 25°C. Then, 8 kg of mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 3:2:2:1). The reactor was sealed and stirred at a speed of 80 r / min for 1 hour to obtain a foamed material.

[0087] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.2 between the foaming material and PM-400, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0088] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 5 layers of alkali-free glass continuous fiber mat (total weight 3.4kg) were evenly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0089] Example 11.

[0090] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0091] Preparation of foaming material: Take 25kg high toughness rigid foam polyether polyol H210 (Nanjing Hongbaoli), 30kg reactive flame retardant polyether polyol EDS-5083X (Jiangsu Changneng), 20kg reactive flame retardant polyester polyol PS-2452 (Jinling Stepan), 25kg high strength rigid foam polyether polyol H5820 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8547 and 2kg surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.25kg catalyst TMR-2, 0.35kg catalyst JXP-508, 0.45kg catalyst The mixture was stirred at a speed of 120 r / min for 20±5 minutes. During the stirring process, the temperature was raised and lowered to ensure that the material temperature was at 25°C. Then, 8 kg of mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 2:2:3:1). The reactor was sealed and stirred at a speed of 80 r / min for 1 hour to obtain a foamed material.

[0092] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.25 between the foaming material and PM-200, and the temperature of the materials was controlled at 22±3°C and the pressure was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0093] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 6 layers of alkali-free glass continuous fiber mat (total weight 4.05kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0094] Example 12.

[0095] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0096] Preparation of foaming material: Take 30kg high-toughness rigid foam polyether polyol NJ-210 (Jurong Ningwu New Materials), 20kg reactive flame-retardant polyether polyol EDS-5083L (Jiangsu Changneng), 30kg reactive flame-retardant polyester polyol PS-2132 (Jinling Stepan), 20kg high-strength rigid foam polyether polyol H5820 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8462 and 1kg surfactant B8490 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.25kg catalyst TMR-2, 0.3kg catalyst JXP-508, 0.45kg catalyst K-15, 0.5kg catalyst JXP-509, 6kg flame retardant TEP and 5kg flame retardant TCPP, 0.25kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, during the stirring process, the temperature was raised and lowered to ensure that the material temperature was 25°C, and then 6kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 2:2:1:1), the reactor was sealed, stirred at a speed of 80r / min for 1 hour, and a foamed material was obtained.

[0097] The materials were pumped into a high-pressure foaming machine at a mass ratio of 1:1.25 between the foaming material and PM-400, and the temperature of the materials was controlled at 22±3°C and the pressure of the materials was controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0098] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 5 layers of alkali-free glass continuous fiber mat (total weight 3.4kg) were evenly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0099] Example 13.

[0100] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0101] Preparation of foaming material: Take 30kg high-toughness rigid foam polyether polyol NJ-310 (Jurong Ningwu New Materials), 30kg reactive flame-retardant polyether polyol F-7190 (Shanghai Xinrui), 20kg reactive flame-retardant polyester polyol PF-2012 (Qingdao Ruinuo), 20kg high-strength rigid foam polyether polyol H5820 (Nanjing Hongbaoli), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8462 and 2kg surfactant B8547 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.35kg catalyst TMR-2, 0.4kg catalyst JXP-508, 0. 25kg catalyst K-15, 0.5kg catalyst JXP-509, 6kg flame retardant TEP and 5kg flame retardant TCPP, 0.3kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, the temperature was raised and lowered during the stirring process to ensure that the material temperature was 25°C, and then 6kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 1:2:2:1), the reactor was sealed, stirred at a speed of 80r / min for 1 hour, and a foamed material was obtained.

[0102] The material is pumped into a high-pressure foaming machine at a mass ratio of 1:1.3 between the foaming material and PM-200, and the material temperature is controlled at 22±3°C and the material pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0103] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 6 layers of alkali-free glass continuous fiber mat (total weight 4.05kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0104] Example 14.

[0105] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0106] Preparation of foaming material: Take 35kg high-toughness rigid foam polyether polyol H210 (Nanjing Hongbaoli), 25kg reactive flame-retardant polyether polyol FR-212 (Yantai Wanhua), 30kg reactive flame-retardant polyester polyol PF-2012 (Qingdao Ruinuo), 10kg high-strength rigid foam polyether polyol NJ-6206 (Jurong Ningwu New Materials), add the above raw materials into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8462 and 1kg surfactant B8547 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.25kg catalyst TMR-2, 0.2kg catalyst JXP-508, 0.15kg Catalyst K-15, 0.4kg catalyst JXP-509, 6kg flame retardant TEP and 4kg flame retardant TCPP, 0.1kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, the temperature was raised and lowered during the stirring process to ensure that the material temperature was 25°C, and then 4kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 2:1:1:0), the reactor was sealed, and stirred at a set speed of 80r / min for 1 hour to obtain a foamed material.

[0107] The material is pumped into a high-pressure foaming machine at a mass ratio of the foaming material to PM-400 of 1:1.35, and the temperature of the material is controlled at 22±3°C and the material pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0108] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 5 layers of alkali-free glass continuous fiber mat (total weight 3.4kg) were evenly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0109] Example 15.

[0110] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0111] Preparation of foaming material: Take 35kg high-toughness rigid foam polyether polyol H310 (Nanjing Hongbaoli), 30kg reactive flame-retardant polyether polyol EDS-5083L (Jiangsu Changneng), 25kg reactive flame-retardant polyester polyol PF-2012 (Qingdao Ruinuo), 10kg high-strength rigid foam polyether polyol NJ-6206 (Jurong Ningwu New Materials), add the above ingredients into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8490 and 2kg surfactant B8547 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.3kg catalyst TMR-2, 0.2kg catalyst JXP-508, 0.05kg catalyst B8490, 0.1kg catalyst B8547, 0.2kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8490 ...490, 0.05kg catalyst B8547, 0.05kg catalyst B8547, 0.05kg catalyst B8490, 0.05kg catalyst B8547, 0.05kg catalyst .1kg catalyst K-15, 0.4kg catalyst JXP-509, 6kg flame retardant TEP and 4kg flame retardant TCPP, 0.1kg distilled water, stir at a speed of 120r / min for 20±5 minutes, increase and decrease the temperature during stirring to ensure that the material temperature is 25℃, then add 4kg mixed foaming agent (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene at 1:1:2:0), seal the reactor, stir at a speed of 80r / min for 1 hour to obtain a foamed material.

[0112] The material is pumped into a high-pressure foaming machine at a mass ratio of 1:1.4 between the foaming material and PM-200, and the material temperature is controlled at 22±3°C and the material pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0113] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 6 layers of alkali-free glass continuous fiber mat (total weight 4.05kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0114] Example 16.

[0115] A multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is prepared by the following method, comprising the following steps:

[0116] Preparation of foaming material: Take 35kg high-toughness rigid foam polyether polyol H310 (Nanjing Hongbaoli), 55kg reactive flame-retardant polyester polyol PF-2012 (Qingdao Ruinuo), 10kg high-strength rigid foam polyether polyol NJ-8238 (Jurong Ningwu New Materials), add the above ingredients into the reactor in the order of low viscosity to high viscosity, add 2kg surfactant B8490 and 2kg surfactant B8462 (Shanghai Evonik), pre-stir for 15±5 minutes, then add 0.1kg catalyst TMR-2, 0.1kg catalyst JXP-508, 0.1kg catalyst K-15, 0. 5kg catalyst JXP-509, 4kg flame retardant TEP and 4kg flame retardant TCPP, 0.1kg distilled water, stirred at a speed of 120r / min for 20±5 minutes, during the stirring process, the temperature was raised and lowered to ensure that the material temperature was 25°C, and then 5kg mixed foaming agent was added (premixed in a cold storage according to the mass ratio of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene of 2:1:2:0), the reactor was sealed, stirred at a speed of 80r / min for 1 hour, and a foamed material was obtained.

[0117] The material is pumped into a high-pressure foaming machine at a mass ratio of 1:1.35 between the foaming material and PM-200, and the material temperature is controlled at 22±3°C and the material pressure is controlled at 120±10kPa for high-pressure mixing to obtain a composite material.

[0118] The alkali-free glass continuous fiber mat CFM981-450 was preheated to a temperature of 30±5°C, and 6 layers of alkali-free glass continuous fiber mat (total weight 4.05kg) were evenly and flatly laid in the mold, and the mold temperature was controlled at 35±5°C; the composite material was evenly poured on the upper part of the alkali-free glass continuous fiber mat using a distribution rod, and the cover film was foamed after the composite material was completely impregnated with the alkali-free glass continuous fiber mat. The foam was demoulded after 6 hours of solidification, and the material was placed in a designated insulation warehouse (temperature controlled at 30±5°C) for 24 hours of internal aging to obtain a polyurethane glass fiber reinforced foam material, which was subjected to a series of performance tests, as shown in Table 2.

[0119] The enhanced cold-insulating foam materials prepared in Examples 1 to 16 were tested, and the performance indicators were tested according to the standards of GB / T40916-2021 and GB / T39936-2021. The test results of each experimental sample are shown in Tables 1 and 2.

[0120] The present invention does not involve parts that are the same as the prior art or can be implemented by using the prior art.

[0121] Table 1. Performance test data of Examples 1 to 9

[0122]

[0123] Table 2. Performance test data of Examples 10 to 16

[0124]

[0125]

Claims

1. A multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material, characterized in that: The foaming material is firstly prepared from the following raw materials in parts by weight: 20 to 50 parts by weight of reactive flame-retardant polyester polyol, 10 to 30 parts by weight of reactive flame-retardant polyether polyol, 15 to 30 parts by weight of high-strength rigid foam polyether polyol, 25 to 35 parts by weight of high-toughness rigid foam polyether polyol, 2 to 5 parts by weight of surfactant, 1.5 to 3 parts by weight of composite catalyst, 10 to 16 parts by weight of flame retardant, 4 to 15 parts by weight of multi-component system foaming agent, and 0.1 to 1.1 parts by weight of water; and then the foaming material is mixed with a mixture of high-functionality isocyanate and diphenylmethane diisocyanate in a mass ratio of 1:1.2 to 1:1.5 to obtain a composite material. , the combined material is uniformly poured on 3 to 10 parts by mass of alkali-free glass continuous fiber felt and completely impregnated with the alkali-free glass continuous fiber felt, and a multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material is obtained by covering film foaming, demoulding, and internal aging; the hydroxyl value of the reactive flame-retardant polyester polyol is 100 to 400 mgKOH / g, the viscosity is 300 to 16000 mPa·s at 25°C, and the functionality is 2 to 5; the hydroxyl value of the high-strength rigid foam polyether polyol is 300 to 500 mgKOH / g, the viscosity is 300 to 10000 mPa·s at 25°C, and the functionality is 4.5 to 8; the high-toughness rigid foam The hydroxyl value of the polyether polyol is 100-350 mgKOH / g, the viscosity is 100-500 mPa·s at 25°C, and the functionality is 2-4; the isocyanate-CNO content of the high-functionality isocyanate and diphenylmethane diisocyanate mixture is 30-33 wt%, the viscosity is 100-600 mPa·s at 25°C, and the functionality is 2.7-3.5; the surfactant is a polyether-polydimethylsiloxane copolymer mixture; the composite catalyst is a combination of at least two of a quaternary ammonium salt catalyst, a trimerization catalyst, a low-odor amine catalyst, and an organic acid salt catalyst; the composite catalyst The mass ratio of the quaternary ammonium salt catalyst, trimerization catalyst, low odor amine catalyst and organic acid salt catalyst is 1:(0.8-1.8):(0.6-1.2):(3.2-4.6); the mass ratio of the composite catalyst is a trimerization catalyst, a low odor amine catalyst and an organic acid salt catalyst is (1.5-8):1:(3.5-11); the mass ratio of the composite catalyst is a trimerization catalyst and an organic acid salt catalyst is 1.5:1; the mass ratio of the composite catalyst is a quaternary ammonium salt catalyst, a trimerization catalyst and a tertiary amine catalyst is (0.5-3):1:(1.5-6); the flame retardant is one or more of triethyl phosphate flame retardant TEP, tri-2-chloropropyl phosphate flame retardant TCPP, tri-2-carboxyethyl phosphine flame retardant TCEP, diethyl ethyl phosphate flame retardant DMPP; when flame retardant TEP and flame retardant TCPP are selected for combination, their mass ratio is (6-10): (2-6); the multi-system foaming agent is one or more of pentafluoropropane, pentafluorobutane, trifluoropropylene, hexafluorobutene; the alkali-free glass continuous fiber mat is a continuous raw fiber mat after surface treatment, and each layer of alkali-free glass continuous fiber mat is synthesized by stacking 20 layers of slender glass fibers; the apparent density of the alkali-free glass continuous fiber mat is 450-600g / m. 2 .

2. The multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material according to claim 1, characterized in that: The multi-component system foaming agent is one or more of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropylene and 1,1,1,4,4,4-hexafluoro-2-butene.

3. The multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material according to claim 1, characterized in that: The multi-system foaming agent is a mixture of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene in a mass ratio of (1-6):(2-5):(1-3):(1-2), or a mixture of 1,1,1,3,3-pentafluoropropane, 1,1,1,3,3-pentafluorobutane, 1-chloro-3,3,3-trifluoropropene and 1,1,1,4,4,4-hexafluoro-2-butene in a mass ratio of (1-3):(1-2):(0-1).

4. The multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material according to claim 1, characterized in that: The alkali-free glass continuous fiber mat is one or more of CFM981-450, CFM985-450, CFM985-600, U809-450, and U801-450; the width of CFM981-450, CFM985-450, and CFM985-600 are all 185 cm, the thickness is all 5 mm, and the apparent density is 450 g / m 2 , 450g / m 2 , 600g / m 2 ; U809-450 and U801-450 have a width of 138cm, a thickness of 6mm, and an apparent density of 450g / m 2 , 450g / m 2 .

5. The multi-component glass fiber reinforced flame retardant low-temperature polyurethane foam material according to claim 1, characterized in that: Continuous strand mats are made of E-glass with the continuous filaments randomly oriented.

6. A method for preparing the multi-system glass fiber reinforced flame retardant low-temperature polyurethane foam material according to claim 1, characterized in that: It includes the following steps: Step 1. Add reactive flame-retardant polyester polyol, reactive flame-retardant polyether polyol, high-strength rigid foam polyether polyol, and high-toughness rigid foam polyether polyol to the reactor in the order of low viscosity to high viscosity, add a surfactant and stir, then add a compound catalyst, a flame retardant, water, and a multi-system foaming agent, and stir to obtain a foaming material; Step 2. Pump the foaming material and the mixture of high-functionality isocyanate and diphenylmethane diisocyanate into a high-pressure foaming machine, control the temperature of the materials to 22±3°C and the pressure to 120±10kPa for high-pressure mixing to obtain a composite material; lay 5 to 8 layers of alkali-free glass continuous fiber felt, evenly pour the composite material until the alkali-free glass continuous fiber felt is completely impregnated, cover the film for foaming, demould, and perform internal aging to obtain a multi-system glass fiber reinforced flame-retardant low-temperature polyurethane foam material.

7. The method according to claim 6, characterized in that: After adding the surfactant, pre-stir for 10 to 20 minutes; then add the composite catalyst, flame retardant and water, stir at a speed of 120 r / min for 10 to 25 minutes, and maintain the material temperature at 25°C during the stirring process; then add the multi-system foaming agent, stir at a speed of 80 to 120 r / min for 1 hour to obtain a foamed material.

8. The method according to claim 6, characterized in that: Mix the foaming material and isocyanate evenly and test them. The foaming material should meet the physical property index at 25°C. The rising time should be 50-80s, the drawing time should be 200-400s, the non-stick time should be 600-800s, and the free foam density should be 60-130kg / m 3 .

9. The method according to claim 6, characterized in that: After laying 5 to 8 layers of alkali-free glass continuous fiber felt in the mold, use a distribution rod to evenly pour the composite material until the alkali-free glass continuous fiber felt is completely impregnated; the internal aging temperature is controlled to be 30±5°C and the time is 24 hours.

10. An application of the multi-component glass fiber reinforced flame retardant low-temperature polyurethane foam material according to claim 1, characterized in that: Used to prepare membrane tanks for storage and transportation of liquefied natural gas.

Citation Information

Patent Citations

  • Polyurethane spraying composition material used for low temperature, cold insulation and flame retardance and preparation method of polyurethane spraying composition material

    CN106674482A

  • Ultra-low-temperature-resistant halogen-free flame-retardant glass fiber reinforced hard polyurethane thermal insulation material produced from environment-friendly foaming agent, and preparation method thereof

    CN107099018A